Turning Over the Keys: Public Prisons, Private Equity, and the Normalization of Markets Behind Bars. Issue 4 (12th December 2021) - Swanson, Jacob; Fainsod Katzenstein, Mary
Abstract : In recent decades, public prisons and jails have increasingly outsourced operational functions by "turning over the keys" to private business and, more recently and specifically, to private equity. By the early 2000s, private equity-owned corporations had entered the core sectors of prison and jail operations, creating "markets behind bars" in telecommunications, commissary sales, health provision, and a range of other services. Two decades later, they have become a quasi-oligopolistic market force across the carceral economy. Reacting to these developments, scholars and activists have explored how private firms generate profits by extracting resources from families of the incarcerated. Less explored is the fact that it is often and particularly private equity firms that partner with public carceral institutions in these extractive practices. In this reflection, we propose a three-part schematic for understanding how such partnerships, with their attendant predation on the poor and people of color, have become normalized. We focus, first, on the mechanism of bureaucracy through which mutual profit-making by public and private entities becomes regularized; second, we explore the legal mechanisms —the apparently small but potent and politically unexamined legal maneuvers—that enable the redirection of family resources beyond the support of a loved one to the operational needs of jails and prisons; finally, we trace the role of gender as a social mechanism through which private equity and its prison/jail partners rely simultaneously on women's traditional role as caretaker and non-traditional role as primary breadwinner. We show that all three mechanisms are crucial to the economic functioning of the carceral state.